Journal of Quantitative Criminology - Weisburd, David; Hasisi, Badi.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Quantitative Criminology focuses on research advances from such fields as statistics, sociology, geography, political science, economics, and engineering. This timely journal publishes papers that apply quantitative techniques of all levels of complexity to substantive, methodological, or evaluative concerns of interest to the criminological community. Features include original research, brief methodological critiques, and papers that explore new directions for studying a broad range of criminological topics.
Keywords: Statistics; Social sciences; Sociology; Criminology and Criminal Justice, general; Sociology, general; Methodology of the Social Sciences; Statistics, general